2015
DOI: 10.1111/bju.13262
|View full text |Cite
|
Sign up to set email alerts
|

Increased use of partial nephrectomy to treat high‐risk disease

Abstract: ObjectivesTo evaluate partial nephrectomy (PN) use in patients at higher risk for clinical progression, using a large national database of American patients. Patients and MethodsWe performed a retrospective review of patients with cN0/ cM0 renal cell carcinoma from 2003 to 2011 using the National Cancer Data Base. Our primary endpoint was PN use for high-risk disease, defined as ≥1 adverse pathological features (APF), namely pT3 stage, high grade, or unfavourable histology. Our secondary endpoint was positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 50 publications
5
14
0
4
Order By: Relevance
“…Furthermore, the present study is the first to show a rise in the use of a minimally invasive PN approach for cT2a tumours, which parallels reported trends for increasing use of minimally invasive PN for cT1a and cT1b masses . Although this is encouraging, any enthusiasm generated by these findings must be tempered by the increased risk of PSMs found by both the present authors and Maurice et al . Indeed, while we noted no difference in PSM rates among PN‐treated cT1a, cT1b and cT2a masses, there was an increase in PSMs overall, attributable to the increased use of minimally invasive approaches over time.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the present study is the first to show a rise in the use of a minimally invasive PN approach for cT2a tumours, which parallels reported trends for increasing use of minimally invasive PN for cT1a and cT1b masses . Although this is encouraging, any enthusiasm generated by these findings must be tempered by the increased risk of PSMs found by both the present authors and Maurice et al . Indeed, while we noted no difference in PSM rates among PN‐treated cT1a, cT1b and cT2a masses, there was an increase in PSMs overall, attributable to the increased use of minimally invasive approaches over time.…”
Section: Discussionsupporting
confidence: 87%
“…6 Our results demonstrate superior or at least equivalent survival for patients with high-risk RCC treated with PN. For RCC with HG/UH or T3, PN was an independent significant predictor of improved OS, after adjusting for age, comorbidity burden, tumour size, and other risk factors for all-cause mortality.…”
Section: Discussionsupporting
confidence: 50%
“…A detailed description of the NCDB has been published previously. 6 We used the NCDB's 2011 participant user file for kidney and renal pelvis cancers. Institutional review board approval was obtained prior to study initiation.…”
Section: Ncdb Participant User Filementioning
confidence: 99%
See 1 more Smart Citation
“…With this growing experience, reports have suggested that partial nephrectomy is being applied to larger and more complex tumors, 8-10 and is being offered to older and multi-morbid patients. 11 While administrative data suggests that partial nephrectomy may improve survival when compared with radical nephrectomy, 12 partial nephrectomy has remained concentrated in high-volume academic centers, and reserved for patients with better insurance and higher socioeconomic status. 13 It is unknown if the increased overall use of partial nephrectomy has benefited patients with impaired pre-operative kidney function, who could benefit most from the procedure.…”
Section: Introduction and Objectivesmentioning
confidence: 99%